Employment problems under socialism - Gernot Gutmann (Intereconomics, 1979)
States with socialist economic systems also suffer from employment problems, a fact which is frequently passed over in silence by the critics of our market economic order. Professor Gernot Gutmann analyses its magnitude and causes.
Keywords: 330; Underemployment